Cognitive functions and special working capacity in elite boxers - Korobeynikov, G.; Korobeinikova, L.; Raab, M.; Baic, M.; Borysova, O.; Korobeinikova, I.; Shengpeng, G.; Khmelnitska, I. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim In the basis of the boxer`s power qualities is the ability to perceive and process external information. Therefore, in order to ensure the proper training of qualified boxers, there is a need to monitor the functional state of the boxer`s organism. The relationship between cognitive functions and special working capacity of elite boxers were studied.